Changing Risk, Return, and Leverage: The 1997 Asian Financial Crisis - Maroney, Neal; Naka, Atsuyuki; Wansi, Theresia (Journal of Financial and Quantitative Analysis, 2004)
Abstract This paper explores risk and return relations in six Asian equity markets affected by the 1997 Asian financial crisis. After the start of the crisis, national equity betas increased and average returns fell substantially. Beta increases due to leverage linked to exchange rates. The increase in expected return needed to accompany this rise in beta is made possible through the creation of capital losses that lower average returns. We propose a new probability-based asset pricing model that captures leverage effects using valuation ratios. Results show the role of leverage in explaining the likelihood of the financial crises. Crosssectional evidence supports time-series findings.